Fatty acid metabolism: target for metabolic syndrome - Wakil, Salih J. (American Society for Biochemistry and Molecular Biology, 2009)
Fatty acids are a major energy source and important constituents of membrane lipids, and they serve as cellular signaling molecules that play an important role in the etiology of the metabolic syndrome. Acetyl-CoA carboxylases 1 and 2 (ACC1 and ACC2) catalyze the synthesis of malonyl-CoA, the substrate for fatty acid synthesis and the regulator of fatty acid oxidation. They are highly regulated and play important roles in the energy metabolism of fatty acids in animals, including humans. They are presently considered as an attractive target to regulate the human diseases of obesity, diabetes, cancer, and cardiovascular complications. In this review we discuss the role of fatty acid metabolism and its key players, ACC1 and ACC2, in animal evolution and physiology, as related to health and disease.